Electrodeposition of Zirconium from 1-Butyl-1-Methylpyrrolidinium-Bis(Trifluoromethylsulfonyl)imide: Electrochemical Behavior and Reduction Pathway. Issue 1 (2nd January 2016) - Vacca, Annalisa; Mascia, Michele; Mais, Laura; Delogu, Francesco; Palmas, Simonetta; Pinna, Alessandra
Abstract : A study on the electrochemical deposition of Zr on platinum, gold, and boron doped diamond (BDD) from 1-butyl-1-methylpyrrolidinium-bis(trifuoromethylsulphonyl) imide is presented in this work. The electrochemical behavior of zirconium ions was investigated by cyclic voltammetries and chronopotentiometries, allowing establishing the mechanism of deposition. Deposition tests were carried out at different potentials and the related samples were analyzed by SEM and EDX. Structural and chemical analyses indicate that the obtained deposits are constituted by metallic zirconium. According to the electrochemistry of zirconium and based on the experimental results, the mechanism is Zr(IV) ⇒ Zr(II) ⇒ Zr.